2017
DOI: 10.1016/j.jmpt.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Standing Sagittal Measurements of Spinal Curvature and Range of Motion in Older Women With and Without Hyperkyphosis Using a Skin-Surface Device

Abstract: Our results indicated that the Spinal Mouse has excellent intrarater reliability for the measurement of sagittal thoracic and lumbar curvature and mobility of the spine in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our findings revealed a perfect correlation for all COM measurements with ICC > 0.9 (CI = 95%) and a likely variation of SEM less than 1°(0.15°≤ SEM ≥ 0.452°), along with a small MDC (0.424°≤ MDC ≥ 1.254°), demonstrating good repeatability of DP measures. These results support previous research indicating that DP is highly consistent and reliable in the clinical detection of postural patterns (29)(30)(31)(32). Our results are very close to what Ashnagar et al reported when studying the reliability of DP for assessing lower extremity alignment in individuals with flatfeet and normal feet types (1.25 -2.78) (33).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed a perfect correlation for all COM measurements with ICC > 0.9 (CI = 95%) and a likely variation of SEM less than 1°(0.15°≤ SEM ≥ 0.452°), along with a small MDC (0.424°≤ MDC ≥ 1.254°), demonstrating good repeatability of DP measures. These results support previous research indicating that DP is highly consistent and reliable in the clinical detection of postural patterns (29)(30)(31)(32). Our results are very close to what Ashnagar et al reported when studying the reliability of DP for assessing lower extremity alignment in individuals with flatfeet and normal feet types (1.25 -2.78) (33).…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, assessment of spinal posture and mobility by SpinalMouse ® provides only surfacebased measures of the curvature of the spine in the frontal and sagittal plane, but it has proven to be reliable [13], feasible, and responsive [27] and is non-invasive. Measurements in the transverse plane of the spine regarding trunk rotations would have made a valuable contribution as it is an important factor in maintaining normal gait patterns [5].…”
Section: Resultsmentioning
confidence: 99%
“…Spinal posture and mobility were assessed using a SpinalMouse ® (Idiag, Fehraltorf, Switzerland), comprising a hand-held inclinometer connected wirelessly to a computer. The SpinalMouse ® was rolled paravertebrally along the spine from the 7th cervical to the 3rd sacral vertebra (rima ani) while the patient was standing barefoot and holding the arms crossed in front of the chest: first with the spine in a neutral upright position, then maximally flexed and, finally, maximally extended; with emphasis on end-range positions of the spine and hips (knees extended) [13]. The SpinalMouse ® software provides a table with inclination angles at each vertebral segment.…”
Section: Spinal Posture and Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The minimally clinical important difference or MCID for changes in spinal curvatures is 10°, [27,28,61] which implies that only changes greater than 10⁰ should be interpreted as a clinically meaningful change. Changes smaller than 10° can be explained by the posture of the patient while taking the X-ray, [62,63] or by the associated measurement error of determining spinal curvature angles. [61] Declaration.…”
Section: Discussionmentioning
confidence: 99%